Monitoring the Heart Rate Variability Responses to Training Loads in Competitive Swimmers Using a Smartphone Application and the Banister Impulse-Response Model - Piatrikova, E.; Willsmer, N. J.; Altini, M.; Jovanovic, M.; Mitchell, L. J. G.; Gonzalez, J. T.; Sousa, A. C.; Williams, S. (International Journal of Sports Physiology and Performance, 2021)
Purpose: First, to examine whether heart rate variability (HRV) responses can be modeled effectively via the Banister impulse-response model when the session rating of perceived exertion (sRPE) alone, and in combination with subjective well-being measures, are utilized. Second, to describe seasonal HRV responses and their associations with changes in critical speed (CS) in competitive swimmers.